Socio-Demographic Factors Influencing Banana Seed Demand among Smallholder Farmers in Uganda: A Cluster Analysis - Ajambo, Susan (not published yet, 2024)
Seed systems facilitate farmers’ access to desirable crop cultivars; hence, a means of investment in improved and adaptable cultivars, and the delivery of genetic gains from breeding and selection of crops. They also support plant health security by using clean planting materials to minimise seed degeneration. Sustainable seed systems must align with the needs of farmers, while presenting opportunities for seed producers to sustain seed supply. Understanding the underlying factors influencing seed demand can enhance the efficiency of banana seed systems to meet the diverse context-specific needs of farmers. Therefore, this study investigates the sociodemographic factors affecting smallholder farmers' perceptions of banana seed demand and their seed acquisition behaviour in Uganda. Understanding the perceived seed demand and seed acquisition patterns could reveal the determinants of banana seed demand. A cluster-based approach was used to study these factors and provide insights into the determinants of off-farm seed sourcing. Multinomial and Tobit regression models were applied to data from 137 banana farmers in Central and Eastern Uganda. Banana seed demand is influenced by both the physical availability of seeds and farmers' sociodemographic characteristics. We identified three farmer clusters with varying perceived seed demands. Perceived seed demand influences farmers’ information-seeking behaviour and seed source diversification, shaping their acquisition strategies. Income, household size, and the sex of the household head were significant predictors of perceived seed demand. A unit increase in income led to a 21.26 unit increase in perceived seed demand (p < 0.001). With each additional household member, the perceived seed shortage reduced by 12.78 units (p = 0.041). Male-headed households experienced a 55.86 units greater perceived shortage than female-headed households did (p = 0.001). These results reveal the underlying heterogeneity in seed demand determinants, which could shape farmer-centric and gender-transformative interventions that address the heterogeneity of smallholder farmers and advocate for a comprehensive multidimensional approach to improve banana seed systems. Our cluster-based analysis introduces a novel approach to studying banana and VPC seed systems.
none
none
Keywords: Banana; VPC seed systems; socio-demographic factors; gender; seed demand; cluster analysis; Uganda